2012
DOI: 10.1111/j.1752-0606.2012.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Coming out, coming home: Helping families adjust to a gay or lesbian child

Abstract: Coming Out, Coming Home is a timely presentation of the struggles and family dynamics related to coming out. In 1996, Doherty and Simmons reported that only 54% of marriage and family therapists (MFTs) felt competent working with GLBTQ clients. Since that time, researchers and educators have been moving toward a more comprehensive and inclusive preparedness in their work on the topic of sexual orientation, in both clinical and training program settings (e. g., Long & Serovich, 2003;Green, Murphy, Blumer, & Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Research has found that the relationship between lesbian and gay youth and their family is often contentious. Lesbian and gay youth found coming out to family members a big challenge (LaSala, 2010;Pistella, Caricato & Baiocco, 2019). After coming out to their family members, lesbian and gay youth experienced not only negative attitudes but also different forms of emotional violence, including emotional rejection or active neglect (Bos et al, 2019;Friedman et al, 2011;Martinez & McDonald, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that the relationship between lesbian and gay youth and their family is often contentious. Lesbian and gay youth found coming out to family members a big challenge (LaSala, 2010;Pistella, Caricato & Baiocco, 2019). After coming out to their family members, lesbian and gay youth experienced not only negative attitudes but also different forms of emotional violence, including emotional rejection or active neglect (Bos et al, 2019;Friedman et al, 2011;Martinez & McDonald, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is an extended literature that documents the often contentious relationship between sexual minority people and their family members (LaSala, 2010;Pistella et al, 2019). It also shows that sexual minority people experienced negative attitudes, emotional violence (Bos et al, 2019;Friedman et al, 2011;Martinez & McDonald, 2017) and physical abuse (Friedman et al, 2011) from their parents and other family members.…”
Section: Discussionmentioning
confidence: 99%
“…The tripartite framework of attitudes conceptualizes attitudes based on three domains: affective/emotional responses, cognitive responses, and behavioral responses (Zanna & Rempel, 2008). These attitudes may, respectively, manifest in negative emotions, disapproval and self‐blaming thoughts, and negative and positive actions (LaSala, 2010). These three domains do not always coincide; for example, a parent may experience negative emotions about their child's LGB identity (e.g., worries about the child's future) but show supportive behaviors (Lin & Hudley, 2009).…”
Section: Tripartite Attitudes Toward Having An Lgb Childmentioning
confidence: 99%